2006
DOI: 10.1189/jlb.0306198
|View full text |Cite
|
Sign up to set email alerts
|

S100B binding to RAGE in microglia stimulates COX-2 expression

Abstract: Besides exerting regulatory roles within astrocytes, the Ca2+-modulated protein of the EF-hand type S100B is released into the brain extracellular space, thereby affecting astrocytes, neurons, and microglia. However, extracellular effects of S100B vary, depending on the concentration attained and the protein being trophic to neurons up to nanomolar concentrations and causing neuronal apoptosis at micromolar concentrations. Effects of S100B on neurons are transduced by receptor for advanced glycation end produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 66 publications
7
95
0
4
Order By: Relevance
“…7,40 TNF-α has an important role in S100B release from the astrocytes, suggesting that TNF-α might elevate the extracellular concentration of S100B favoring activating effects of S100B on microglia. 7,40 Collectively, our data and previously demonstrated mechanisms indicate that S100B contributes to the activation and progression of neuroinflammatory processes following TBI. However, S100B inhibition may directly or indirectly attenuate neuroinflammation after TBI, and future studies are needed to determine the mechanisms of S100B-mediated neuroinflammatory effects.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Imentioning
confidence: 99%
See 3 more Smart Citations
“…7,40 TNF-α has an important role in S100B release from the astrocytes, suggesting that TNF-α might elevate the extracellular concentration of S100B favoring activating effects of S100B on microglia. 7,40 Collectively, our data and previously demonstrated mechanisms indicate that S100B contributes to the activation and progression of neuroinflammatory processes following TBI. However, S100B inhibition may directly or indirectly attenuate neuroinflammation after TBI, and future studies are needed to determine the mechanisms of S100B-mediated neuroinflammatory effects.…”
Section: S100b Does Not Influence Key Microglial Activation Markers Imentioning
confidence: 99%
“…6 In contrast, as an extracellular factor S100B interacts with advanced glycation end product-specific receptor (AGER) to exert beneficial or detrimental effects, or pro-proliferative or pro-differentiative consequences based on its concentration and microenvironment. 7,8 In addition to its expression in astroglia and Schwann cells, S100B has also been found in adipocytes, chondrocytes, cardiomyocytes, lymphocytes, bone marrow cells, and melanocytes where it exerts intracellular and extracellular functions. 6 Therefore, both CNS and circulatory S100B exert the same functions that are dependent on their concentration and may serve as important biomarkers of CNS injury.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that S100B is only expressed by a subtype of mature astrocytes that ensheath blood vessels and by NG2-expressing cells. Recent studies[4,5] have provided more detailed information about the mechanism (s) of action of S100B as an intracellular regulator and an extracellular signal. Intracellular S100B acts as a stimulator of cell proliferation and migration and an inhibitor of apoptosis and differentiation, which might have important implications during the development and repair of the brain, cartilage and skeletal muscle, the activation of astrocytes in the course of brain damage and neurodegenerative processes, and the remodeling of cardiomyocytes after infarction as well as in melanomagenesis and gliomagenesis.…”
Section: Introductionmentioning
confidence: 99%